A simple electrochemical method for Cd(II) determination in real samples based on carbon nanotubes and metal-organic frameworks. Issue 16 (16th December 2022) - Yu, Ling; Wan, Jing-Wei; Meng, Xian-Zhu; Gu, Hui-Wen; Chen, Ying; Yi, Hong-Chao
ABSTRACT: The establishment of a simple and effective method for determination of heavy metal ions has great significance due to the high hazard of heavy metal ions to public health and environments. Herein, we developed a facile way to synthesise a nanocomposite comprised of carbon nanotubes (CNTs) and metal-organic frameworks (MOFs), and explored its application in constructing an electrochemical (EC) sensor for detection of Cd 2+ in aqueous solutions. The sensing surface was simply fabricated by casting a drop of CNTs-MOFs nanocomposite onto the electrode. After drying at room temperature, the modified electrode was immersed in a Cd 2+ -containing acetate buffer solution to accomplish the EC measurement. The morphology of materials was characterised by SEM. The EC characterisations validated the good conductivity and excellent Cd 2+ -responsive property of CNTs-MOFs. As expected, the analytical performance for Cd 2+ determination was satisfactory with a wide linear detection range of 0.3 μM-150 μM, a limit of detection (LOD) of 0.2 μM and good selectivity. Detection of Cd 2+ in real samples was also realised. Moreover, if under other potentials, even the analysis of other heavy metal ions such as Pb 2+ and Cu 2+ can be achieved with our sensing platform. This work provided a versatile way for detecting heavy metal ions in complicated samples.